Synthesis and application of novel bonded cationic β-cyclodextrin derivatives as chiral stationary phases for supercritical fluid chromatography - Liu, Maolong. (2009)
A novel cationic β-cyclodextrin derivative named mono-6A-(3-vinylimidazolium)-6A-deoxyperphenylcarbamoylated-β-cyclodextrin chloride was synthesized by selective tosylation and vinylimidazole substitution followed by perfunctionalisation with phenylcarbamate groups. The fully derivatized β-cyclodextrin was then immobilized onto a vinylized silica gel to provide new chiral stationary phases (CSPs). The immobilization of the derivative was performed through a radical co-polymerization reaction with AIBN as the initiator in the help of different small molecular monomers. Two monomers were used to help co-polymerization, namely 2,3-dimethyl-1,3-butadiene (DMBD) and methylmethacrylate (MMA). Their effects on immobilization and enantioselective capabilities of CSPs were investigated. The performance of CSPs prepared was evaluated on supercritical fluid chromatography (SFC) using a wide range of racemic drugs as test analysts such as β-blockers, flavanone compounds, profens, dansyl-amino acids, etc which are of high medical values. Good separations were achieved for flavanone compounds, dansyl-amino acids and some of the non-protolytic drugs. The enantiodiscriminatory properties of the CSPs were found to be affected mainly by the phenylcarbamate groups of β-cyclodextrin derivative and also the cationic imidazole spacer arm at the primary rim. The selection of modifier in mobile phase was found to be racemate type-dependent, and addition of small amount acidic additive into modifier can improve the separation efficiency and reduce peak broadening of acidic samples without compromising the selectivity. Generally, CSP immobilized using DMBD has a better performance than that of MMA.